Duration of changes in physical and hydraulic properties of a clayey Oxisol by mechanical chiseling - Drescher, Marta Sandra; Reinert, Dalvan José; Denardin, José Eloir; Gubiani, Paulo Ivonir; Faganello, Antônio; Drescher, Gerson Laerson (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to determine the duration of the effects of soil decompaction, by mechanical chiseling, through physical and hydraulic indicators of a clayey Oxisol under no‑tillage (NT). The treatments consisted of months (0, 6, 12, 18, 24, 30, and 36) after chiseling under NT and of a control treatment without chiseling under NT during 27 years. The following variables were evaluated: penetration resistance, infiltration rate, bulk density and relative density, pore size distribution, and saturated hydraulic conductivity. The duration of the effects of mechanical chiseling varied according to the evaluated soil property, lasting six months for bulk density and relative density, total porosity, and macroporosity; 18 months for penetration resistance; and 24 months for hydraulic conductivity and infiltration rate. Soil properties related to water transport, such as hydraulic conductivity and steady infiltration rate, maintain the effect of mechanical chiseling for a longer time and, therefore, are more suitable to measure the duration of mechanical decompaction.